Beyond Software Architecture Creating and Sustaining Winning Solutions - Hohmann, Luke (Addison Wesley Professional, 2003)
Annotation
Includes bibliographical references and index
Keywords: Computer software; Computer architecture; Software; Computer Software; Computer Architecture; Computers; General; Computers; Systems Architecture; General; Logiciels; Ordinateurs; Architecture; software; Engineering & Applied Sciences; Computer Science